2018
DOI: 10.21273/horttech03845-17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ‘Castellana’ Virgin Olive Oils with Regard to Olive Ripening

Abstract: The production of high-quality virgin olive oil from traditional olive (Olea europaea L.) varieties with peculiar and differential characteristics is of great interest for the olive oil market. ‘Castellana’ is an autochthonous variety mainly located in the center of Spain. The aims of this study were 1) the characterization of ‘Castellana’ virgin olive oils and 2) the evaluation of the influence of fruit ripening degree on the oil quality to establish an optimum harvest time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 34 publications
2
29
2
Order By: Relevance
“…In fact, oil content accumulates in olive fruits as the ripening progresses (Motilva et al, 2000;Dag et al, 2011;Bakshi et al, 2018;Sönmez et al, 2018). In the same trend, Benito et al (2013) and Mena et al (2018) reported an increase in the industrial oil yield during olive maturation.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In fact, oil content accumulates in olive fruits as the ripening progresses (Motilva et al, 2000;Dag et al, 2011;Bakshi et al, 2018;Sönmez et al, 2018). In the same trend, Benito et al (2013) and Mena et al (2018) reported an increase in the industrial oil yield during olive maturation.…”
Section: Introductionsupporting
confidence: 57%
“…The industrial oil yield (extracted oil), given in percentage of fresh olive paste weight (W) and considering the olive oil density (D) at ambient temperature of 0.915 g.mL À1 , was determined using the formula (Mena et al, 2018):…”
Section: Oil Extractionmentioning
confidence: 99%
“…; Mena et al . ) and emphasises the importance of olives (and olive oil) as a valuable source of vitamin E in our diet.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the sensory characteristics of the different monovarietal oils of the PDOs found in literature are reported in Table 2. In the case of the Castellana variety, according to the literature [11] its oil possesses quite high values as well: 3.3 for bitterness and 4.0 for pungency. On the contrary, in the case of Manzanilla cacereña and Cornezuelo oils a lower score in these two positive attributes is observed: for example, 1.2 and 0.5 for bitterness respectively as compared to 4.2 for Cornicabra (unstructured 10 cm scale; www.advancedsciencenews.com www.ejlst.com Table 2).…”
Section: Quality Characteristicsmentioning
confidence: 98%
“…According to its product specification, its protected EVOO is obtained from the fruit of the olive tree (Olea europea L.) exclusively of the Cornicabra cultivar, by mechanical procedures or other physical means that do not produce alteration in the oil, preserving the flavor, aroma and characteristics of the olive fruit from which it is manufactured. [10,11] Municipalities belonging to the agrarian counties of Mancha, Pastos y Campo de Montiel, all of them in the province of Ciudad Real, are covered by the PDO Aceite Campo de Montiel (EU 543/ 2010, 21 June 2010). From the sensory www.advancedsciencenews.com www.ejlst.com point of view this PDO oil presents a medium to intense scores for the positive attributes of fruity, bitter, and pungent.…”
Section: Protected Designation Of Origin In the Central Iberian Peninmentioning
confidence: 99%